Reduced in vitro T-cell responses induced by glutaraldehyde-modified allergen extracts are caused mainly by retarded internalization of dendritic cells - Heydenreich, Bärbel (Blackwell Science Inc, 2012)
Although allergen-specific immunotherapy is a clinically effective therapy for IgE-mediated allergic diseases, the risk of IgE-mediated adverse effects still exists. For this reason, chemically modified allergoids have been introduced, which may destroy IgE-binding sites while T-cell activation should be retained. The aim of the study was to analyse the differences between intact allergens and differently modified/aggregated allergoids concerning their internalization as well as T-cell and basophil activation. For this purpose human monocyte-derived immature dendritic cells (DC) were incubated with Phleum pratense or Betula verrucosa pollen extract or with the corresponding allergoids, modified with formaldehyde or glutaraldehyde. After an additional maturation process, the antigen-loaded mature DC were co-cultured with autologous CD4(+) T cells. Allergenicity was tested by leukotriene release from basophils. In addition, the uptake of intact allergens and allergoids by immature DC was analysed. The proliferation of, as well as the interleukin-4 (IL-4), IL-10, IL-13 and interferon-γ production by, CD4(+) T cells which had been stimulated with glutaraldehyde allergoid-treated DC was reduced compared with CD4(+) T cells stimulated with intact allergen-treated or formaldehyde allergoid-treated DC. In line with this, glutaraldehyde-modified allergoids were more aggregated and were internalized more slowly. Furthermore, only the allergoids modified with glutaraldehyde induced a decreased leukotriene release by activated basophils. These findings suggest that IgE-reactive epitopes were destroyed more efficiently by modification with glutaraldehyde than with formaldehyde under the conditions chosen for these investigations. Glutaraldehyde-modified allergoids also displayed lower T-cell stimulatory capacity, which is mainly the result of greater modification/aggregation and diminished uptake by DC.